2019
DOI: 10.1039/c9dt02195g
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic analysis of a new family of monomeric diphosphinoboranes

Abstract: A series of monomeric amino- and aryl(diphosphino)boranes has been synthesized and structurally characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…From the large family of diphosphinoboranes recently synthesized by our group, 11 we selected compounds 1/1 ′ and 2 for reactivity studies ( Chart 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the large family of diphosphinoboranes recently synthesized by our group, 11 we selected compounds 1/1 ′ and 2 for reactivity studies ( Chart 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the X-ray analysis of 1 indicated that the interactions between P and B atoms lead to a structure with one double and one single PB bond, nuclear magnetic resonance (NMR) analysis, as well as DFT calculations, revealed that this is not the most energetically favorable conformation. 11 Computational studies elucidated that both 1 and lowest-energy 1′ ( Chart 1 ), in which P–B distances are comparable and both phosphorus atoms are pyramidal (see Figures S42 and S45 ), are energetically accessible at the crystallization temperature. 11 Otherwise, in the case of diphosphinoborane 2 , the B atom is substituted by the amino group, and in this case, the N-lone pair and P-lone pairs compete for donation to the empty p-orbital of boron.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…due to p-donor or carborane substituents) and phosphorus thus retains its lone pair and tetrahedral geometry, are highly electron rich h 1 ligands for transition metal complexes. [9][10][11] By far the most common route for the construction of P-B bonds is salt elimination [12][13][14][15][16][17][18][19] using an alkali metal phosphide, MPR 2 , and a haloborane (Scheme 1A), although other routes are known, including nucleophilic addition of a boryl anion to a chlorophosphine (B), 20 elimination of silyl halide (C), 10,11,21 and cross-coupling of a B-I species with secondary phosphines using a palladium catalyst (D). 9 Of the different synthetic options for the construction of phosphorus-carbon bonds, hydrophosphination of unsaturated carbon substrates has gained popularity in recent years.…”
Section: Introductionmentioning
confidence: 99%